Floristic Richness of Peddagattu-sherepally Area, a Proposed Site for Uranium Projects, Nalgonda District, Telangana State, India - Baleeshwar Reddy, A.; Vasudeva Rao, V.; Vijaya Bhasker Reddy, A. (Indian Forester, 2018)
The study was carried out in ordered to explore the existing floristic composition in Pedagattu- Sherepally area, Nalgonda district, Telangana state, which is a proposed site for uranium projects. The study area harbours 464 species under 324 genera and 86 families. Of the total 464 species, dicotyledons are represented by 373 species belonging to 258 genera under 70 families and 89 monocotyledon species belonging to 64 genera and 14 families. Habit wise analysis showed that herbs (239) most predominated species followed by shrubs (100), trees (89), aquatic forms (24) and climbers (12). The family Poaceae is the dominated family followed by Fabaceae, Asteraceae, Caesalpiniaceae, Euphorbiaceae and Acanthaceae. The present study collected a total 21 endemic species belonging to 19 genera and 12 families and total of 83 medicinal plant species belonging to 43 families and 73 genera were recorded. The proposed site for uranium projects coming to exist the flora of the study area would effect and altered.